Pembelajaran Daring: Ancaman Perusahaan EdTech Pada Sekolah Ditengah Pandemi Covid-19 - Atyanta Nika Rumaksari (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
Covid-19 forces the traditional classroom learning method to go online; while teachers nowadays struggle to adapt to this new technology, the EdTech firm's market is increasing. That 44 startups were categorized as Unicorn in 2020. Rather than just referring to the analysis of EdTech's functions that help schools conventionally, this study also looks at the theory of economic-based interaction between education-based organizations that threaten schools' meaning and function that shift during this pandemic to online. Based on this premise, we can identify the features of EdTech, which overlap with conventional schools. Our method is conducting Descriptive Analysis based on observed data derived from validated formal research and put them into three dimensional business model patterns to get evidence of the organization’s strategic or tactical operations. This research aims to address whether the emerging of EdTech firms becomes a threat to traditional schools. This work also finds the core value, which drives student's motivation toward learning outcomes in Indonesia. Based on the research, superior ICT technology adaptation plays an essential key in educational activities. It means that EdTech can provide dependence on schools which not yet comply with these features so that when they had cooperation, EdTech can direct or even changing the school’s original values. This cooperation dependency can challenge the school’s operation cost, increasing the risk of supply and management, involving consumer-related decision-making that always benefited EdTech rather than schools.